PENGEMBANGAN SOAL NUMERASI MATEMATIKA MATERI PECAHAN BERKONTEKS LINGKUNGAN UNTUK SISWA SEKOLAH DASAR KELAS V DI UPTD SD NEGERI 1 SAMALANGA - Fajria, Annisa; Mislinawati; Intan Safiah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop valid environmental context-based mathematics numeracy problems on fraction topics for fifth-grade elementary school students. The research employed a qualitative approach using Research and Development (R&D) design based on the Tessmer model, consisting of preliminary and formative evaluation stages (self-evaluation, expert reviews, one-to-one, small group, and field test). Research subjects were fifth-grade students of UPTD SD Negeri 1 Samalanga, involving 3 students in the one-to-one stage, 6 students in the small group stage, and 30 students in the field test stage. Research instruments included interview guidelines, questionnaires, validation sheets, and test item sheets. Data analysis techniques included document analysis, Likert scale analysis for theoretical validity, as well as empirical validity analysis, item discrimination index, and item difficulty level analysis. Results indicated that the development process using the Tessmer model was carried out systematically and resulted in 35 numeracy items with 7 environmental context-based story texts. All items met theoretical validity criteria with 100% feasibility percentage based on expert validator assessments. Based on empirical validity testing, 29 items (82.86%) were declared valid. The developed environmental context-based mathematics numeracy problems on fraction topics are appropriate for use as assessment instruments for fifth-grade elementary students' numeracy skills.